2004
DOI: 10.1016/j.molcel.2004.08.007
|View full text |Cite
|
Sign up to set email alerts
|

The p53-Induced Oncogenic Phosphatase PPM1D Interacts with Uracil DNA Glycosylase and Suppresses Base Excision Repair

Abstract: The wild-type p53-induced phosphatase PPM1D (or Wip1) is a serine/threonine phosphatase that is transcriptionally upregulated by p53 following ultraviolet and ionizing radiation. PPM1D is an oncogene in transformation assays and is amplified or overexpressed in several human tumor types. Here, we demonstrate that PPM1D interacts with the nuclear isoform of uracil DNA glycosylase, UNG2, and suppresses base excision repair (BER). Point mutations that inactivate PPM1D phosphatase activity abrogate BER suppression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
136
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(141 citation statements)
references
References 44 publications
5
136
0
Order By: Relevance
“…26 More recently, it has been shown that Wip1 associates with the nuclear isoform of uracil DNA glycosylase, UNG2, and that Wip1 suppresses DNA damage-induced base excision repair (BER) activity by dephosphorylating and inactivating UNG2. 30 In this study, we show that Wip1 interacts with Chk2 both physically and functionally in the nuclei. Wip1 dephosphorylates Thr68 in activated Chk2 both in vitro and in vitro, and inactivates Chk2 kinase activity toward Cdc25C.…”
Section: Introductionmentioning
confidence: 53%
See 1 more Smart Citation
“…26 More recently, it has been shown that Wip1 associates with the nuclear isoform of uracil DNA glycosylase, UNG2, and that Wip1 suppresses DNA damage-induced base excision repair (BER) activity by dephosphorylating and inactivating UNG2. 30 In this study, we show that Wip1 interacts with Chk2 both physically and functionally in the nuclei. Wip1 dephosphorylates Thr68 in activated Chk2 both in vitro and in vitro, and inactivates Chk2 kinase activity toward Cdc25C.…”
Section: Introductionmentioning
confidence: 53%
“…Interestingly, it has been recently reported that Wip1 dephosphorylates the nuclear form of uracil DNA glycosylase (UNG2) and Chk1, thereby suppressing BER and intra-S and G2/M checkpoint regulation, respectively. 30,40 In the case of UNG2 and p38, phosphorylation sites on these molecules, which can be targets for Wip1-mediated dephosphorylation, reveal consensus sequences 'phospho-T-X-phospho-Tyr (Y) (or phospho-T-X-Y, X: optional a.a.)'. 41 In this respect, it is important to note that our in vitro evidence as well as previous report 40 indicate the presence of additional target sequences for Wip1, which are 'phospho-S-Q' or 'phospho-T-Q', well-known fingerprints of ATM kinase (see Table 1).…”
Section: Antagonistic Effect Of Wip1 On Chk2-dependent Apoptosismentioning
confidence: 99%
“…In each case, this modification has been observed to increase catalytic activity and hence may regulate BER initiation [97,98]. On the other hand, TDG, MPG and NEIL2 are modified and regulated by acetylation (Table III).…”
Section: Modification Of Proteins That Initiate Ber Via Lesion Recognmentioning
confidence: 97%
“…Wip1 also dephosphorylates p38 and UNG2 at pT180GY and pT6LY sites, respectively (Takekawa et al, 2000;Lu et al, 2004). In the case of the p38 MAP kinase, the TGY motif is part of the activation loop of the kinase and is diphosphorylated on Thr and Tyr residues when p38 is activated.…”
Section: Wip1 Phosphatase Antagonizes Chk2 Activation M Oliva-trastoymentioning
confidence: 99%
“…Third, Wip1 directly inhibits Chk1 by dephosphorylating the ATR-targeted phosphoSer345 (Lu et al, 2005). In addition, Wip1 directly dephosphorylates and inhibits a uracil N-glycosylase (Ung2) implicated in the base excision repair of DNA (Lu et al, 2004). The overexpression of Wip1 is likely to be oncogenic given its antagonism of key proteins involved in maintaining genomic stability.…”
Section: Introductionmentioning
confidence: 99%